Sharing ownership, profits, and decision-making in the 21st century - Kruse, Douglas (Emerald, 2013)
Ownership and decision-making are key issues in the economic restructuring taking place as economies struggle to emerge from the Great Recession, and technological change and globalization continue to place new demands on workers and firms. Corporate, labor, and policy leaders are increasingly recognizing the potential role of employee ownership, cooperatives, profit sharing, and other ways in which employees directly participate in decision-making and financial performance. This volume contains cutting-edge research on the causes and effects of financial and decision-making participation, including results from the United States, European Union, Russia, India, and Basque area of Spain, along with a unique laboratory experiment to probe the real-world findings. Along with consideration of standard economic outcomes are studies that examine job satisfaction in the largest U.S. worker cooperative, and firm survival among cooperatives and ESOP companies. In addition, there are theoretical and thought pieces on the meaning and value of employee ownership in a rapidly changing world economy.
Includes index.
Keywords: Management -- Employee participation.; elektronické knihy; electronic books